Cardiovascular disease risk factor profile of experienced male amateur marathon runners: A systematic review - O`Riordan, C.; Savage, E.; Newell, M.; Flaherty, G.; Hartigan, I. (Sports Health: A Multidisciplinary Approach, 2023)
Context: Male amateur marathon runners represent a unique subset of the population who may be at increased risk of cardiovascular disease (CVD) due to their underlying risk factors and their involvement in vigorous exercise such as marathon running.